Fenomenologi Spiritual Experience Pada Mualaf Yang Berlatar Belakang Kristen - Mahesya, Wigy Gories; Triwijati, N.K. Endah; Fuadhy, Regisda Machdy (AL-ADYAN, 2021)
A mualaf must go through a long process before deciding to do a conversion. That process of religious conversion might allows mualaf run into spiritual experience. The aim of this research article is to describe the spiritual experience who experienced by mualaf that previously a Christian. Spiritual experience is a series event that are unusual, unpredictable, and have ultimate meaning. This research used qualitative research method and used a phenomenological paradigm. The participants in this research consisted of two people who converted their religion from Christianity to Islam. The result of this research is that spiritual experience who experienced by every single person is not same. Spiritual experience in religious conversion that experienced by participants can give positive impact for their lives. So it can be concluded that by spiritual experience, participants will get a deeper understanding of religion and can interpret their lives.